The Cultural Interaction and Local Identity Formation at the Beteng Sari Archaeological Site, East Lampung - Endang Indika Yustina; Karsiwan (CV. Yazri Aksara Nusantara, 2026)
The Beteng Sari Archaeological Site in East Lampung represents a socio-historical landscape shaped by long-term cultural interaction within the civilizational networks of the Indonesian archipelago. It is concluded that Betengng Sari as a space of cultural interaction and dynamic local identity formation, moving beyond the predominantly descriptive approaches of previous research. Employing a qualitative historical case study design, the research is based on field observations, in-depth interviews, and the analysis of archaeological remains and written sources. The main findings indicate that the configuration of earthen fortifications and ditches, the distribution of domestic artifacts, the presence of Chinese ceramics, metal objects, ancient coins, and a cosmologically oriented burial complex demonstrate Beteng Sari’s integration into regional trade networks and cultural mobility. The coexistence of megalithic traditions, Hindu–Buddhist influences, early Islamic remains, and imported material culture reveals a layered process of acculturation characterized by continuity and adaptation rather than cultural replacement. It is concluded that Beteng Sari functioned as an interregional node of interaction in which local agency played a crucial role in shaping spatial organization, social practices, and collective memory, thereby framing local identity in East Lampung as a contextual and non-essentialist historical construction, with theoretical implications for studies of cultural interaction and landscape archaeology. Situs Purbakala Beteng Sari di Lampung Timur merepresentasikan lanskap sosial-historis yang terbentuk melalui interaksi budaya jangka panjang dalam jaringan peradaban Nusantara. Penelitian ini bertujuan menganalisis Beteng Sari sebagai ruang interaksi budaya dan pembentukan identitas lokal yang dinamis, melampaui pendekatan deskriptif yang selama ini mendominasi kajian situs. Penelitian menggunakan pendekatan kualitatif dengan desain studi kasus historis melalui observasi lapangnon-esensialismendalam, serta analisis tinggalan arkeologis dan sumber tertulis. Temuan utama menunjukkan bahwa konfigurasi benteng dan parit, sebaran artefak domestik, kehadiran keramik Cina, artefak logam, uang kuno, serta kompleks makam berorientasi kosmologis menegaskan keterhubungan Beteng Sari dengan jaringan perdagangan dan mobilitas budaya regional. Koeksistensi tradisi megalitik, pengaruh Hindu–Buddha, Islam awal, dan budaya material impor mengindikasikan proses akulturasi berlapis yang berlangsung melalui kesinambungan dan adaptasi, bukan penggantian budaya. Disimpulkan bahwa Beteng Sari berfungsi sebagai simpul interaksi lintas wilayah, di mana agensi masyarakat lokal berperan penting dalam membentuk tatanan ruang, praktik sosial, dan memori kolektif, sehingga identitas lokal Lampung Timur dapat dipahami sebagai konstruksi historis yang kontekstual dan non-esensialis, dengan implikasi teoretik bagi kajian interaksi budaya dan arkeologi lanskap.